Άγνωστο βενετικό διάταγμα παραχώρησης γαιών στον Γεώργιο Κονεμένο (24 Αυγούστου 1727) - Καράμπελας, Νίκος Δ. (Peri Istorias, 2022)
In our article we present the previously unknown Venetian Decree issued on 24th August 1727 by Francesco Correr, Superintendent General of the Sea (Provveditore General da Mar) of the Most Serene Republic of Venice. The Decree grants a large piece of land, in the area of Preveza, at the border with the Ottoman State, to Corporal (caporale) Georgios Konemenos, in recognition of his services to the Doge. We also present a topographic plan of the Site of Skafidaki (Sitto di Scaffidachi), which determined the boundaries of the land granted to Konemenos, and which, in our opinion, accompanied the Decree. The plan was drawn by the Venetian military engineer Santo Semitecolo on 14th October 1727, and refers to Georgios Konemenos as Captain (capitan). Information about Georgios Konemenos and his two sons, Christos and Apostolis, is presented too.